Pair of bosses (2), Crosby Hall - Unknown (Tufts Archival Research Center, 2005)
This illustration is from the plate "Remains of Crosby Hall, Bishopsgate Street" in the History and Antiquities of London, Westminster, Southwark and parts adjacent, vol. 3, by Thomas Allen.